Presentation binary information by paraphase code in highly productive parallel computing systems - Жуков, І.А.; Гуменюк, В.О. (Proceedings of National Aviation University (archive), 2005)
The motives for existing and beginning the automatic checkup problem generally in computers and particularly in highly productive parallel computing systems are considered. The possibility of application the code, named as a paraphase one, in such systems with the purpose of increasing the productivity and the reliability level of the computing results is analyzed. A new approach to computing operations organization is proposed with taking into account the peculiarities of such binary information presentation in parallel computing systems.